Malnutrition with Secondary Hypothyroidism in Children: A Case Report and Pathophysiological Review of Patients in One of the Hospitals in Surabaya - Puspita, Angela; Setiadi, Alexander Wignyo (Journal La Medihealtico, 2025)
Malnutrition in children remains a global health problem that has a broad impact on growth, development and metabolic balance. One complication that receives less attention is secondary hypothyroidism, a condition that occurs due to metabolic adaptation to prolonged energy deficit. This situation can worsen the patient's prognosis and increase the risk of neurological complications and infections. This case report aims to describe the clinical course of a child with severe malnutrition who experienced secondary hypothyroidism and discuss the pathophysiological mechanisms underlying the link between malnutrition and thyroid dysfunction. Case: A 2 year 1 month old boy with a body weight of 5 kg (< -3 SD) and a height of 69 cm presented with complaints of diarrhea, fever, recurrent cough and episodes of seizures. Laboratory examination showed leukocytosis, increased CRP, and electrolyte disturbances. Evaluation of thyroid function revealed low FT4 levels (0.85 ng/dL) with depressed TSH (0.19 µIU/mL), leading to a diagnosis of secondary hypothyroidism. Metabolic adaptations due to malnutrition lead to decreased production of thyroid binding proteins as well as low TSH secretion in response to metabolic stress. This situation contributes to a slowdown in metabolism and worsens nutritional recovery, as well as increasing the risk of infectious and neurological complications. The literature supports that secondary hypothyroidism in children with malnutrition is reversible with optimal nutritional recovery. A multidisciplinary approach that includes clinical stabilization, electrolyte correction, and monitoring of thyroid function is very important in the management of children with malnutrition and secondary hypothyroidism.